VIKSIT BHARAT AND THE ROLE OF RURAL WOMEN - Chanu, Laishram Pratima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rural-urban divide continues to be an unresolved issue in India, even seven decades after India gained independence. Without a comprehensive understanding of rural livelihoods especially those of women, the aspiration of achieving a self-reliant Bharat cannot be realized. This study investigates the frequently overlooked roles of rural women and delves into the challenges they encounter in their daily lives. The study is based on various reviewed research papers, websites, books, and reports. The study also draws on insights obtained from semi-structured interviews that include open-ended questions. For sample collection, three Panchayats in Thoubal District, Manipur, were chosen randomly. The essential findings include financial constraints, political impediments, societal constructs, healthcare hurdles, etc. These gaps can be resolved with government intervention, a shift in women’s own perspectives, more investment in skill development, and improved awareness initiatives.